(untitled) (Economic studies journal, 2021)
Abstract The study aims to identify the impact of organizational trust on organizational immunity at the private Libyan commercial banks in Al-Jabal Al-Akhdar region. To achieve the study aims, the correlational descriptive method is applied. Therefore, the researchers has developed a questionnaire based on some previous studies, which they were sure of their validity and reliability. The study population included all All employees at the Private Libyan commercial banks in Al-Jabal Al-Akhdar region, They were about (124) employee. The study followed the method of the comprehensive survey, and after the distribution of the questionnaire, (101) form were retrieved as valid for statistical analysis. The Statistical Package for the Social Sciences program (SPSS) was used to analyze the associated questionnaire data. The study concluded the follow results: Firstly, the overall level of the organizational trust at the commercial banks was high. Secondly, the level of organizational immunity was aslo very high. Thirdly, there was a statistically significant effect of organizational trust on organizational immunity. Finally, the study provided a set of recommendations to Strengthening the Organizational immunity and Organizational trust reinforcement at commercial banks under study.